(untitled) (Research, Society and Development, 2022)
Introduction: Persistent elevation in plasmatic parathyroid hormone (PTH) concentrations is responsible for a problem known as hyperparathyroidism, classified according to the origin of the breakdown of normal physiology. At the secondary hyperparathyroidism (SHPT), there is some metabolic dysfunction that leads to stimulation of the parathyroid glands, such as chronic kidney disease (CKD), the most common cause. Parathyroidectomy (PTX) has some indications in the treatment of SHPT, however, approaches such as diet adequacy, vitamin D replacement or use of drugs that control PTH secretion generate more benefits to patients than surgical intervention. Objective: To conduct a database literature review on available therapies for patients with secondary hyperparathyroidism. Methodology: A survey of articles was carried out over a period of 5 years in the Pubmed database on available therapies for patients with SHPT, finding, in the end, 19 articles. Results and Discussion: From this analysis, it was observed that new calcium-mimetics such as Etelcalcetide and Evocalcet proved to be an alternative to Cinalcacet, as they have similar efficacy and safety, but with advantages regarding use and adherence. In addition to these, Colecalciferol and Paricalcitol (calcitriol analogues) and DP0001 (new vitamin D receptor activator) are efficient in reducing serum PTH. Conclusion: Despite pointing out promising alternatives, all studies had limitations. Therefore, other studies must be developed, with a goal of defining pharmacological and technical resources capable of superimposing the treatments currently adopted.